Anticonvulsant prophylaxis and steroid use in adults with metastatic brain tumors: summary of SNO and ASCO endorsement of the Congress of Neurological Surgeons guidelines*. Issue 4 (18th March 2019) - Chang, Susan M; Messersmith, Hans; Ahluwalia, Manmeet; Andrews, David; Brastianos, Priscilla K; Gaspar, Laurie E; Gatson, Na Tosha N; Jordan, Justin T; Khasraw, Mustafa; Lassman, Andrew B; Maues, Julia; Mrugala, Maciej; et al.
Abstract: Background: The Congress of Neurological Surgeons (CNS) has developed a series of guidelines on the treatment of adults with metastatic brain tumors, including systemic therapy and supportive care topics. ASCO has a policy and set of procedures for endorsing clinical practice guidelines that have been developed by other professional organizations. Methods: Two CNS Guidelines were reviewed for developmental rigor by methodologists and an independent multi-disciplinary Expert Panel was formed to review the content and assess agreement with the recommendations. The expert panel voted to endorse the two guidelines and ASCO and SNO independently reviewed and approved the ASCO/SNO guideline endorsement. Results: The ASCO/SNO Expert Panel determined that the recommendations from the CNS anticonvulsants and steroids guidelines, published January 9, 2019, are clear, thorough, and based upon the most relevant scientific evidence. ASCO/SNO endorsed these two CNS guidelines, with minor alterations. Conclusions: Key recommendations include: prophylactic anti-epileptic drugs were not recommended for routine use; corticosteroids (specifically dexamethasone) were recommended for temporary symptomatic relief in patients with neurologic symptoms and signs related to mass effect from brain metastases.